If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 + -16 * 4 = 0 Multiply -16 * 4 -12 + -64 = 0 Combine like terms: -12 + -64 = -76 -76 = 0 Solving -76 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 4(z+6)-26= | | 4x/7x+28 | | 1-6x=19+3x | | 4x/27+8x | | 2(5z-1)-2(6-2z)=4 | | 3(2z-2)-3(5-3z)=3 | | 3y/4=0.6 | | 60-3(E-5)= | | -3x+8x^2+1=0 | | 3(r-4)=3 | | -2b=10-8.58 | | 5h+9=4h+1 | | 3L+22=9l-20 | | 6-3f=18 | | 1.4t-12=-0.6t | | 1.4t-12=4x+23 | | x^2-2bx+a^2=0 | | 500+45(5)=y | | 500+45x=y | | 0.4xsquared-40x+360=0 | | z^2+4iz+5=0 | | x+5y/x | | 3(x-7)-4(x+2)=20 | | (x+5y)/x | | 4x-1=64 | | 7/11=x/45 | | 5x+0.9= | | 7x+0.2= | | 1/3(7x-1)=1/4 | | 81=9a | | 182/7+(5*11)=9a | | 12+144+20+6/7+(5*11)=9a |